2022
DOI: 10.1371/journal.pone.0258876
|View full text |Cite
|
Sign up to set email alerts
|

Poly-glutamine-dependent self-association as a potential mechanism for regulation of androgen receptor activity

Abstract: The androgen receptor (AR) plays a central role in prostate cancer. Development of castration resistant prostate cancer (CRPC) requires androgen-independent activation of AR, which involves its large N-terminal domain (NTD) and entails extensive epigenetic changes depending in part on histone lysine demethylases (KDMs) that interact with AR. The AR-NTD is rich in low-complexity sequences, including a polyQ repeat. Longer polyQ sequences were reported to decrease transcriptional activity and to protect against … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The liquid–liquid phase separation (LLPS) especially acts on the dysregulation of epigenetics, which could lead to the tumorigenesis and tumor progression [ 21 , 22 , 23 ]. A number of recent studies consider LLPS as a novel therapeutic target of cancer intervention [ 21 ], similarly in prostate cancer [ 19 ]. However, there were limited studies that focused on exploring the correlation between LLPS and PCa, especially the BCR of PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liquid–liquid phase separation (LLPS) especially acts on the dysregulation of epigenetics, which could lead to the tumorigenesis and tumor progression [ 21 , 22 , 23 ]. A number of recent studies consider LLPS as a novel therapeutic target of cancer intervention [ 21 ], similarly in prostate cancer [ 19 ]. However, there were limited studies that focused on exploring the correlation between LLPS and PCa, especially the BCR of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting LLPS-mediated transcription factor (TF) and the formation of LLPS on enhancers to reprogram treatment-resistant tumor cells for preventing the progression of PCa seemed feasible [ 16 , 18 ]. Another study hypothesized that polyQ-dependent LLPS could potentially provide new therapies against castration-resistant prostate cancer (CRPC) by leading to the inhibition of transcriptional activity of AR [ 19 ]. However, to our knowledge, the studies which focus on exploring the correlation between LLPS and PCa, especially the BCR of PCa, are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that AR forms condensates in the nucleus, and elevated nuclear localization was observed despite decreased transcriptional activity with increasing length of polyQ1 ( 202 ). This work is very preliminary, and further studies will be needed to elaborate whether increase in polyQ1 length results in phase separation and/or aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the AR-DBD was identified as a minimal region capable of driving LLPS in the presence of polyU ( 201 ). Another recent study showed that the length of the polyQ affects nuclear localization and hence the transcriptional activity of AR ( 202 ). This suggests that despite AR-NTD being insufficient for driving LLPS alone, it still has a regulatory role, probably by determining solubility via the length of the polyQ1 and recruiting co-factors that can alter the LLPS propensity.…”
Section: Current Research Gapsmentioning
confidence: 99%
See 1 more Smart Citation